Desafios da inclusão na educação infantil: reflexões a partir do estágio curricular - Almeida, Tainara dos Santos (Universidade Federal do Tocantins, 2025)
The inclusion of students with special needs in the regular education system is a widely discussed need in the educational field. The process of inclusion in early childhood education, involving planning and adaptation of environments, materials and pedagogical practices, can ensure not only the right to access to quality education, but, above all, adequate learning and development of children. Using Brazilian educational legislation such as the Education Guidelines and Bases Law (BRASIL, 1996), the Convention on the Rights of Persons with Disabilities (BRASIL, 2006), the Guidelines for Special Educational Assistance (BRASIL, 2009), the Law Brazilian Institute of Inclusion (BRASIL, 2015) we discussed inclusion in Early Childhood Education. This research's primary objective is to understand how the inclusion of children with special needs in early childhood education develops, based on a public institution in the municipality of Miracema do Tocantins, TO. The approach that guides the study is qualitative in nature, based on participant observation, carried out throughout the supervised curricular internship of the Pedagogy course. Data analysis demonstrated that there is a significant effort by the teaching staff and also the school team to build an inclusive environment, aimed at meeting the demands presented by children with special needs, however, there are many daily obstacles to improving the conditions offered, among them, the following stood out: infrastructure, teaching materials, rigid routines and the need for teacher training and qualifications.